Digestibility of finely ground, cracked, and rolled milo grain. - Smith, E.F.; Parrish, D.B. (Kansas Agricultural Experiment Station, 2012)
A digestion trial was conducted with 12 steers which were allotted into three lots of 4 steers each. A ration of sorghum silage (Tennessee Orange), soybean oil meal pellets and milo grain, salt and ground limestone was fed to each lot. Lot 1 received finely ground milo, Lot 2 cracked milo, and Lot 3 rolled milo.
Keywords: Beef; Milo; Digestibility